1997
DOI: 10.1038/bjc.1997.588
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma risk and residence in sunny areas

Abstract: Summary Melanoma risk among subjects from Germany, France and Belgium who had lived for 1 year or more in sunny climates was examined in a one-to-one unmatched case-control study conducted among white subjects 20 years old or more. A total of 412 consecutive patients with melanoma diagnosed from 1 January 1991 onwards, were derived from hospital registers; 445 controls were randomly chosen in the same municipality as the cases. After adjustment for host characteristics, melanoma risk associated with residence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Furthermore, sun exposure in childhood has been implicated to be of special importance for future melanoma risk, even if sun exposure during adulthood also is of significance. 23,24 The decline in melanoma incidence also in the middle-aged population lends support to the idea that UV radiation not only is involved in melanoma initiation, but also during tumor promotion and progression. 25 The still increasing incidence in the older population might also reflect a greater importance of cumulative sun exposure in melanoma genesis at older ages, as suggested by the divergent pathway hypothesis.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, sun exposure in childhood has been implicated to be of special importance for future melanoma risk, even if sun exposure during adulthood also is of significance. 23,24 The decline in melanoma incidence also in the middle-aged population lends support to the idea that UV radiation not only is involved in melanoma initiation, but also during tumor promotion and progression. 25 The still increasing incidence in the older population might also reflect a greater importance of cumulative sun exposure in melanoma genesis at older ages, as suggested by the divergent pathway hypothesis.…”
Section: Discussionmentioning
confidence: 89%
“…22,23 Similar findings were found in a case-control study involving European patients among whom arrival before age of 10 years to a sunny location of residence (such as the Mediterranean) conferred a fourfold increased risk of developing melanoma. 24 However, a previous systematic review considered case-control studies to constitute of lower-quality evidence due to the inherent difficulties of measuring historical sun exposure. 9 Earlier studies in Israel reported a onethird lower risk among European migrants to Israel compared to Israeli-born Jews.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, migrant studies have documented that the risk of melanoma occurrence or of death is two to three times greater among light-skinned subjects born in Australia than among subjects of European descent who migrated to Australia after 15 years [31,32]. Melanoma risk in adult life seems to be low in the absence of sun exposure during childhood [33,34]. Animal experiments have shown that susceptibility to UVinduction of melanoma is greatest just after birth [35][36][37].…”
Section: Discussionmentioning
confidence: 99%